On-line analytical processing tools for land revenue management system - Sahibuddin, Shamsul; Zakaria, Nor Hawaniah (2000)
A functional data warehouse organizes and stores all of the available data needed for informational, analytical processing over a historical time perspective. The whole purpose of building the data warehouse is to give an identified set of users a particular set of data. This study is focusing on data analysis tools for tbe land revenue system used by a state government. Land Office is one of the major revenue providers for tbe state government. According to the report provided by the land office in one of the states in 1999, the total income collected through land office was more than RM15 million [61. A system was developed in 1995 to facilitate the collection process. This system is called Sistem Pentadbiran Basil Tanah (SPHT) or Land Revenue Management System. This paper will describe bow a data analytical tool is going to be implemented in the system in order to provide a better mechanism in the decision-making process. New system architecture is proposed in order to maintain the existing system while at the same time providing new analytical processing tools capabilities. Issues regarding the database architecture are also discussed.